Rare earth doped light switchable upconversion nanocomposite particles and preparation method and application thereof

By designing a rare earth doped structure in light switchable upconverting nanoparticles, the ability to independently emit red, blue and green light under excitation of three near-infrared light sources is solved, and it is difficult to achieve pure three primary color upconversion luminescence in the prior art. Problem, it has unique luminous characteristics and efficient optical properties.

CN116463115BActive Publication Date: 2025-02-14SHANGHAI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310519905.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-10
Publication Date
2025-02-14
Estimated Expiration
2043-05-10

AI Technical Summary

Technical Problem

Existing light switchable upconverting nanoparticles are difficult to achieve pure upconversion of red, green and blue primary colors in a single nanoparticle, especially under excitation of three near-infrared light sources.

Method used

By designing rare earth doped light, the up-converting nanocomposite particles can be switched, and NaErF4 nanoparticles are used as the core, and the three shells of NaYbF4, NaYbF4:Nd and NaYF4:Yb, Tm are successively coated to achieve independent excitation under 808nm, 980nm and 1550nm The ability to emit red, blue, and green light.

Benefits of technology

It realizes that red, blue and green light independently emits under excitation of three near-infrared light sources, with unique luminous characteristics of three excitation-three emissions, and the emission color is independent of the power density of the laser.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116463115B_ABST
    Figure CN116463115B_ABST
Patent Text Reader

Abstract

The present invention provides a rare earth doped light switchable upconversion nanocomposite material and its preparation method and application. The first aspect of the present invention provides a rare earth doped light switchable upconversion nanocomposite material, which uses NaErF4 nanoparticles as the core, and the outer surface of the core is coated with a first shell layer, a second shell layer, and a third shell layer in sequence, wherein the first shell layer includes NaYbF4, the second shell layer includes NaYbF4:Nd, and the third shell layer includes NaYF4:Yb,Tm. The rare earth doped upconversion nanocomposite material provided by the present invention has a three-excitation-three-emission luminescence characteristic, that is, by coating fewer shell layers, it can achieve independent emission of red light, blue light and green light under the excitation of three near-infrared light sources (808nm, 980nm and 1550nm).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rare earth doped light switchable up-conversion nano composite particle and a preparation method and application thereof, and relates to the technical field of nano biomaterials. Background Art

[0002] The emission spectrum of photoswitchable upconversion nanoparticles (UCNPs) can be precisely controlled by changing the external excitation light source, making them widely used in optical display, information anti-counterfeiting, biological imaging and diagnosis and treatment. However, most of the photoswitchable upconversion nanoparticles reported so far are generally limited to orthogonal emission (such as red-green, green-blue, red-blue, etc.) with dual excitation (such as 980nm and 808nm excitation), while the upconversion luminescence of the three primary colors (red, green, and blue) as an indispensable component of full-color emission plays a vital role in many applications, but there is currently a lack of research on the three excitation and three emission of single UCNPs, especially the emission of pure red, green, and blue primary colors.

[0003] Generally speaking, in order to achieve the excitation-emission characteristics of photoswitchable upconversion nanoparticles, it is usually necessary to dope different activator ions in different shell layers of core-shell upconversion nanoparticles, which also leads to the impure emission color of the nanoparticles to a certain extent. Summary of the invention

[0004] The present invention provides a rare earth doped light switchable up-conversion nano composite particle and a preparation method thereof, which can independently emit red light, blue light and green light under the excitation of three near-infrared light sources (808nm, 980nm and 1550nm).

[0005] The present invention also provides application of the rare earth doped light switchable up-conversion nanocomposite particles in imaging and treating tumor cells.

[0006] The first aspect of the present invention provides a rare earth doped light switchable up-conversion nanocomposite particle, wherein the composite particle has a NaErF4 nanoparticle as a core, and the outer surface of the core is sequentially coated with a first shell layer, a second shell layer and a third shell layer;

[0007] The first shell layer includes NaYbF4;

[0008] The second shell layer includes NaYbF4:Nd;

[0009] The third shell includes NaYF4:Yb,Tm.

[0010] The light-switchable upconversion nanocomposite particles provided by the present invention have a core-shell structure. Figure 1The schematic diagram of the structure of the light-switchable upconversion nanocomposite particles UCNPs provided by the present invention is as follows: Figure 1 As shown in the figure, the core of the composite particle is NaErF4 nanoparticles, and the surface of the core is coated with three layers of shells in sequence, and each shell contains different rare earth elements to achieve green, red and blue upconversion luminescence. The specific luminescence mechanism is: under the excitation of 1550nm laser, Er in the core 3+ As both an activator and a sensitizer, first 3+ Absorbs energy from 1550nm, from the ground state 4 I 15 / 2 Energy level, non-radiative transition to excited state 4 I 13 / 2 , 4 I 9 / 2 , 2 F 9 / 2 , 2 H 11 / 2 The energy levels realize red and green light emission respectively, but because Yb in the first shell NaYbF4 3+ The existence of 3+ of 4 I 9 / 2 The energy released by the energy level relaxation is transferred to Yb 3+ of 2 F 5 / 2 energy level, and this part of the energy is finally absorbed by the defects of the first shell, thereby reducing the emission of red light and resulting in enhanced green light emission (545nm). Under 808nm laser excitation, the Nd 3+ Absorbs photons from 808nm and transfers them to Yb 3+ of 2 F 5 / 2 Energy level, because there are Yb in the first and second shells 3+ The existence of Er enables multi-layer energy transfer, and finally the energy reaches the core 3+ of 4 I 11 / 2 , 2 F 9 / 2 , 2 F 7 / 2 energy level, and because the core has 100% Er 3+ , due to the cross relaxation process, it leads to strong red light emission (655nm). Under 980nm laser excitation, the third shell Yb 3+ Absorbs 980nm energy and then transfers the energy to Tm 3+ , Tm 3+ Reached by multiphoton absorption 1 G4, 1The D2 energy level leads to strong blue light emission (475nm). Therefore, the present invention independently emits red light, blue light and green light under the excitation of three near-infrared light sources (808nm, 980nm and 1550nm) through different rare earth doping elements.

[0011] In a specific embodiment, the upconversion energy migration path can be precisely controlled by the thickness of the shell layer and the doping ratio of the rare earth element. Specifically: the thickness of the first shell layer is 2.5-6.1nm; the thickness of the second shell layer is 2.7-6.8nm; the thickness of the third shell layer is 17.8-35.3nm.

[0012] Furthermore, in the second shell layer, the molar ratio of Yb to Nd is 8:2.

[0013] Furthermore, in the third shell layer, the molar ratio of Y, Yb and Tm is 80:19.5:0.5.

[0014] The second aspect of the present invention provides a method for preparing the rare earth doped light-switchable upconversion nanocomposite particles as described above, comprising the following steps:

[0015] Step 1, mixing an Er source, an inorganic fluoride and a sodium source and reacting them to prepare NaErF4 nanoparticles;

[0016] Step 2, dispersing NaErF4 nanoparticles in a solvent, adding a Yb source, an inorganic fluoride and a sodium source, so that the surface of the NaErF4 nanoparticles is coated with a first shell layer containing NaYbF4, to obtain first particles;

[0017] Step 3, dispersing the first particles in a solvent, adding a Yb source, a Nd source, an inorganic fluoride and a sodium source, so that the surface of the first particles is coated with a second shell layer containing NaYbF4:Nd, to obtain second particles;

[0018] Step 4: Disperse the second particles in a solvent, add a Y source, a Yb source, a Tm source, an inorganic fluoride and a sodium source, so that the surface of the second particles is coated with a third shell layer containing NaYF4:Yb, Tm, and obtain the rare earth-doped light-switchable upconversion nanocomposite particles.

[0019] In a specific embodiment, the preparation method comprises the following steps:

[0020] Step 1: Mix an Er source, an inorganic fluoride and a sodium source and react them to prepare NaErF4 nanoparticles.

[0021] Specifically, first, the Er source is dispersed and dissolved in a mixed solvent of oleic acid and octadecene, and a clear and transparent first solution is prepared after dehydration and degassing; secondly, an inorganic fluoride and a sodium source are dissolved in a solvent (for example, methanol) at room temperature to obtain a second solution; then, the second solution is added to the first solution, the temperature of the mixed solution is increased, and the solvent methanol is stirred and removed; finally, the reaction system is evacuated and reacted under an inert gas atmosphere to obtain NaErF4 nanoparticles; after the reaction is completed, the NaErF4 nanoparticles are cleaned with cyclohexane for standby use.

[0022] Step 2, dispersing NaErF4 nanoparticles in a solvent, adding a Yb source, an inorganic fluoride and a sodium source, so that the surface of the NaErF4 nanoparticles is coated with a first shell layer containing NaYbF4, to obtain first particles;

[0023] Specifically, first, the NaErF4 nanoparticles prepared in step 1 are dispersed in a solvent (for example, cyclohexane), the Yb source is dissolved in a mixed solvent of oleic acid and octadecene, and water and gas are removed to obtain a clear and transparent third solution, the NaErF4 nanoparticle solution is added to the third solution, and maintained at 100-150°C for 0.5-1h to remove the cyclohexane solvent; secondly, the inorganic fluoride and the sodium source are dissolved in methanol, added to the above-mentioned mixed system, the temperature of the mixed solution is increased and stirred to remove the solvent methanol; finally, the reaction system is evacuated, and the reaction is carried out under an inert gas atmosphere to obtain the first particles.

[0024] Furthermore, the molar ratio of the NaErF4 nanoparticles to the Yb source is 0.1:(0.3-1).

[0025] Step 3, dispersing the first particles in a solvent, adding a Yb source, a Nd source, an inorganic fluoride and a sodium source, so that the surface of the first particles is coated with a second shell layer containing NaYbF4:Nd, to obtain second particles;

[0026] Specifically, the first particles are dispersed in a solvent by a method similar to step 2, the Yb source and the Nd source are dispersed in a mixed solvent of oleic acid and octadecene, and the coating reaction is carried out by the same method to obtain the second particles.

[0027] Furthermore, the molar ratio of the first particles to the Yb source is 0.05:(0.16-0.4), and the molar ratio of the first particles to the Nd source is 0.05:(0.04-0.1).

[0028] Step 4, dispersing the second particles in a solvent, adding a Y source, a Yb source, a Tm source, an inorganic fluoride and a sodium source, so that the surface of the second particles is coated with a third shell layer containing NaYF4:Yb,Tm, to obtain the rare earth doped upconversion nanocomposite material;

[0029] Furthermore, in step 4, the molar ratio of the second particles to the Y source is 0.03:(0.4-2), the molar ratio of the second particles to the Yb source is 0.03:(0.05-0.5), and the molar ratio of the second particles to the Tm source is 0.03:(0.002-0.02).

[0030] In step 1-4, the mass ratio of oleic acid to octadecene is 1:(2-2.5), and the mass ratio of inorganic fluoride to sodium source is 1:(1-1.5).

[0031] In step 1-4, the Er source is erbium acetate, the Yb source is ytterbium acetate, the Nd source is neodymium acetate, the Tm source is thulium acetate, the Y source is yttrium acetate, the inorganic fluoride is ammonium fluoride, and the sodium source is sodium hydroxide.

[0032] The third aspect of the present invention provides the application of the rare earth doped light switchable upconversion nanocomposite particles in tumor cell imaging and treatment.

[0033] The rare earth-doped light-switchable upconversion nanocomposite particles provided in the first aspect of the present invention can be used in tumor cell imaging and treatment by adsorbing tumor cell imaging and therapeutic drugs on their surface.

[0034] In a specific embodiment, the application mechanism is as follows Figure 2 As shown, when rare earth-doped light-switchable upconversion nanocomposite particles are adsorbed with photosensitizers, the green light emitted under 1550nm excitation can be absorbed by the photosensitizer, thereby generating reactive oxygen to kill tumor cells; the heat generated by the red light emitted under 808nm excitation can also have a certain killing effect on tumor cells; the blue light emitted under 980nm excitation can be used for real-time monitoring of cell imaging, which helps to achieve integrated diagnosis and treatment and has good application prospects.

[0035] It can be understood that the material adsorbed on the surface of the rare earth-doped light-switchable upconversion nanocomposite particles can be a photosensitizer, or one or more of an anti-tumor drug and a radiotherapy sensitizer.

[0036] In a specific embodiment, tumor cell imaging and adsorption of therapeutic drugs can be achieved by coating a silica coating layer having a mesoporous structure on the surface of rare earth-doped light-switchable upconversion nanocomposite particles. The specific preparation method includes:

[0037] Step 1: disperse rare earth-doped light-switchable upconversion nanocomposite particles in cyclohexane solvent, and at the same time, dissolve an organic template (e.g., CTAB) in deionized water, mix and stir the two solutions evenly, add a silicon source (e.g., TEOS) to react, and after the reaction is completed, cool to room temperature and collect solid particles.

[0038] Further, based on 50 mg of the rare earth-doped light-switchable upconversion nanocomposite particles, the volume of the silicon source TEOS used is 300-400 μL.

[0039] Step 2: Mix the rare earth-doped light-switchable upconversion nanocomposite particles coated with the mesoporous structure with the desired adsorbed substance, so that the substance is adsorbed in the mesoporous structure to obtain composite particles adsorbed with tumor cell imaging and therapeutic drugs.

[0040] Furthermore, the tumor cell imaging and therapeutic drug is a photosensitizer, and the photosensitizer includes FePc and MC540.

[0041] The implementation of the present invention has at least the following advantages:

[0042] 1. The light-switchable up-conversion nanocomposite particles provided by the present invention have a core-shell structure, wherein the core is NaErF4 nanoparticles, and the surface of the core is sequentially coated with three shell layers, and each shell layer contains different rare earth elements. Through the design of different rare earth doping elements, the light-switchable up-conversion nanocomposite particles provided by the present invention independently emit red light, blue light and green light under the excitation of three near-infrared light sources (808nm, 980nm and 1550nm), realizing a unique three-excitation-three-emission luminescence characteristic, and the emission color is independent of the power density of the laser.

[0043] 2. The present invention achieves precise control of the upconversion energy migration path by changing the thickness of different light-emitting layers or the doping concentration of light-emitting ions.

[0044] 3. By adsorbing and loading tumor cell imaging and therapeutic drugs on the surface of rare earth-doped light-switchable upconversion nanocomposite particles, its application in tumor cell imaging and treatment can be realized. At a concentration of 300 μg / mL, the cell survival rate can still reach more than 95%. It has excellent biocompatibility and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 A schematic diagram of the structure of the rare earth-doped light-switchable up-conversion nanocomposite material provided by the present invention;

[0046] Figure 2 A schematic diagram of the principle of application of the rare earth-doped light-switchable upconversion nanocomposite material provided by the present invention in tumor cell imaging and treatment;

[0047] Figure 3The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the first particles with first shell layers of different thicknesses under 1550 nm excitation are shown, wherein (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the green-red ratio;

[0048] Figure 4 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the second particles with different thicknesses of the second shell layer under 808 nm excitation are shown, wherein (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the red-green ratio;

[0049] Figure 5 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the second particles with different thicknesses of the second shell layer under 1550 nm excitation are shown, wherein (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the green-red ratio;

[0050] Figure 6 The up-conversion fluorescence emission spectra of the absolute intensity and relative intensity of the second particles with different Yb doping amounts under 808nm excitation, where (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the red-green ratio;

[0051] Figure 7 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the second particles with different Yb doping amounts under 1550nm excitation, where (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the green-red ratio; Figure 8 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the third particles with different thicknesses of the third shell under 980 nm excitation, wherein (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the blue-red ratio;

[0052] Fig. 9 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the third particles with different thicknesses of the third shell under 808 nm excitation, wherein (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the red-to-blue ratio;

[0053] Fig.10 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the third particles with different thicknesses of the third shell layer under 1550 nm excitation, wherein (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the green-red ratio;

[0054] Fig.11 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the third particles with different Yb doping amounts under 980nm excitation, where (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the blue-red ratio;

[0055] Fig.12 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the third particles with different Yb doping amounts under 808nm excitation, where (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the red-to-blue ratio;

[0056] Fig.13 The absolute intensity and relative intensity of up-conversion fluorescence emission spectra of the third particles with different Yb doping amounts under 1550nm excitation, where (a) is the absolute intensity, (b) is the relative intensity, and (b inset) is the green-red ratio;

[0057] Fig.14 Comparison of the luminescence intensity of C@S1@S2@S3 UCNPs at different powers under 1550nm, 808nm, and 980nm excitation;

[0058] Fig.15 : are electron microscope images of the core particle, the first particle, the second particle and the rare earth-doped light-switchable upconversion nanocomposite particle, wherein a is the electron microscope image of the core particle NaErF4, b is the electron microscope image of the first particle, c is the electron microscope image of the second particle, d is the electron microscope image of the rare earth-doped light-switchable upconversion nanocomposite particle, and the inset is the crystal spacing measurement image of the rare earth-doped light-switchable upconversion nanocomposite particle under a high-power electron microscope;

[0059] Fig.16 The Yb in the rare earth doped light switchable up-conversion nanocomposite particles provided by the present invention 3+ 、Nd 3+ , Er 3+ , Y 3 + 、Tm 3+ Element mapping diagram of ions;

[0060] Fig.17 TEM characterization results of UCNPs@mSiO2;

[0061] Fig.18 is the N2 adsorption / desorption isotherm of UCNPs@mSiO2, and the inset in the upper left corner is the pore size distribution diagram;

[0062] Fig.19 The infrared thermal images of UCNPs@mSiO2-MC540-FePc solutions with different concentrations changing with time under 808nm laser irradiation;

[0063] Fig. 20The ultraviolet absorption spectrum of the nanocomposite UCNPs@mSiO2-MC540-FePc containing 1,3-diphenylisobenzofuran (DPBF) probe irradiated by 1550nm laser within 30min;

[0064] Fig.21 The DPBF consumption of the nanocomposite UCNPs@mSiO2-MC540-FePc containing 1,3-diphenylisobenzofuran (DPBF) probe under 1550nm laser irradiation at different experimental conditions;

[0065] Fig. 22 Cell survival rate after incubation of HeLa cells with different concentrations of UCNPs@mSiO2-MC540-FePc for 24 h;

[0066] Fig.23 The survival rate of HeLa cells under six different experimental conditions with different concentrations of UCNPs@mSiO2-MC540-FePc;

[0067] Fig.24 The up-conversion fluorescence emission spectra of NaErF4:Yb(20%), Nd(20%), Tm(0.5%) nanoparticles under 808nm excitation;

[0068] Fig.25 The up-conversion fluorescence emission spectra of NaErF4:Yb(20%), Nd(20%), Tm(0.5%) nanoparticles under 980nm excitation;

[0069] Fig.26 The up-conversion fluorescence emission spectra of NaErF4:Yb(20%), Nd(20%), Tm(0.5%) nanoparticles under 1550nm excitation;

[0070] Fig. 27 This is the upconversion fluorescence emission spectrum of C@S2@S1@S3 nanoparticles under 808nm excitation;

[0071] Fig.28 This is the upconversion fluorescence emission spectrum of C@S2@S1@S3 nanoparticles under 980nm excitation;

[0072] Fig.29 This is the upconversion fluorescence emission spectrum of C@S2@S1@S3 nanoparticles under 1550nm excitation. DETAILED DESCRIPTION

[0073] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] Example 1

[0075] This embodiment provides a method for preparing a rare earth doped light-switchable upconversion nanocomposite material, comprising the following steps:

[0076] Step 1: Synthesis of NaErF4 nanoparticles:

[0077] Weigh 1.0 mmol of dry Er(CH3COO)3 solid powder, 6 mL of oleic acid (OA) and 15 mL of 1-octadecene (ODE) into a 100 mL three-necked flask, raise the temperature to 150°C under continuous magnetic stirring (stirring speed is 570 rpm-600 rpm), and keep warm for about 30 min to dissolve the Er(CH3COO)3 solid powder to obtain a clear and transparent solution.

[0078] The solution was cooled to below 60°C, 6 mL of methanol solution containing 100 mg NaOH and 150 mg NH4F was dripped dropwise into the three-necked flask, and the temperature was raised to 120°C and kept warm for 40 min to remove the methanol in the solution.

[0079] The vacuum was initially evacuated for 20 min, and the mixture was heated to 300 °C in an argon atmosphere and kept at this temperature for 1 h to synthesize nanoparticles with uniform morphology and no impurities.

[0080] After the reaction is completed, turn off the heating, and after the solution is cooled to room temperature, the solution in the three-necked flask is divided into centrifuge tubes, an equal volume of anhydrous ethanol is added, and the precipitate is collected by high-speed centrifugation, washed with cyclohexane and anhydrous ethanol solution to obtain NaErF4 nanoparticles, which are stored in 20 mL of cyclohexane.

[0081] Step 2: Preparation of core / shell structured NaErF4@NaYbF4 nanoparticles:

[0082] Weigh 0.3 mmol of solid powder of Yb(CH3COO)3, 12 mL of oleic acid (OA) and 30 mL of 1-octadecene (ODE) into a 100 mL three-necked flask, and heat to 150°C under continuous magnetic stirring (stirring speed of 570 rpm-600 rpm) and keep warm for about 30 min to obtain a clear and transparent solution.

[0083] The solution was cooled to below 80°C, 5 mL of NaErF4 cyclohexane solution (the molar amount of NaErF4 is 0.1 mmol) was added to a three-necked flask, the temperature was raised to 150°C with stirring, and the temperature was kept for about 40 min to remove the cyclohexane in the solution, and then the temperature was lowered to below 60°C, and 5 mL of a prepared methanol solution containing 25 mg NaOH and 22.5 mg NH4F was dripped dropwise into the three-necked flask, and the mixture was continued to be heated to 110°C and kept for 30 min to remove the methanol in the solution.

[0084] The vacuum was initially evacuated for 30 minutes, and the temperature was raised to 300° C. in an argon atmosphere and kept at that temperature for 70 minutes, so as to coat the surface of the NaErF 4 nanoparticles with a first shell layer containing NaYbF 4 .

[0085] After the reaction is completed, turn off the heating. After the solution is cooled to room temperature, the solution in the three-necked flask is divided into centrifuge tubes, an equal volume of anhydrous ethanol is added, and the precipitate is collected by high-speed centrifugation. It is washed several times with cyclohexane and anhydrous ethanol solution to obtain NaErF4@NaYbF4 upconversion nanoparticles (C@S1), which are stored in 20 mL of cyclohexane.

[0086] Step 3: Preparation of NaErF4@NaYbF4@NaYbF4:Nd nanoparticles:

[0087] Weigh 0.24mmol Yb(CH3COO)3 and 0.06mmol Nd(CH3COO)3 solid powders, 12mL oleic acid (OA) and 30mL octadecene (ODE) into a 100mL three-necked flask, heat to 150°C under continuous magnetic stirring (stirring speed is 570rpm-600rpm), and then keep warm for about 30min to obtain a clear and transparent solution.

[0088] Turn off the heating, cool down to below 80℃, take 5mL of the synthesized NaErF4@NaYbF4 cyclohexane solution ( NaErF4@ The molar amount of NaYbF4 is 0.05 mmol) was added into a three-necked flask, heated to 150°C with stirring, and kept warm for about 40 min to remove cyclohexane in the solution. The solution was then cooled to below 60°C, and 5 mL of a methanol solution containing 25 mg NaOH and 22.5 mg NH4F was dripped dropwise into the three-necked flask. The mixture was heated to 110°C and kept warm for 30 min to remove methanol in the solution.

[0089] The first particle was evacuated for 30 minutes and heated to 300° C. in an argon atmosphere and kept at this temperature for 70 minutes to coat the surface of the first particle with a second shell layer containing NaYbF4:Nd.

[0090] After the reaction is completed, turn off the heating. After the solution is cooled to room temperature, the solution in the three-necked flask is divided into centrifuge tubes, an equal volume of anhydrous ethanol is added, and high-speed centrifugation is performed to obtain a precipitate, which is washed several times with cyclohexane and anhydrous ethanol solution to obtain NaErF4@NaYbF4@NaYbF4:20% Nd upconversion nanoparticles (C@S1@S2), which are stored in 20 mL of cyclohexane.

[0091] Step 4: Preparation of NaErF4@NaYbF4@NaYbF4:Nd@NaYF4:Yb,Tm nanoparticles:

[0092] Weigh 1.2mmol Y(CH3COO)3, 0.2925mmol Yb(CH3COO)3 and 0.0075mmol Tm(CH3COO)3 solid powders, 12mL oleic acid (OA) and 30mL 1-octadecene (ODE) into a 100mL three-necked flask, heat to 150°C under continuous magnetic stirring (stirring speed is 570rpm-600rpm), and then keep warm for about 50min to obtain a clear and transparent solution.

[0093] Turn off the heating, cool down to below 80℃, take 5mL of the synthesized NaErF4@NaYbF4@NaYbF4:20%Nd cyclohexane solution ( The molar amount of NaErF4@NaYbF4@NaYbF4:20% Nd is 0.03 mmol) was added into a three-necked flask, heated to 150°C with stirring, and kept warm for about 40 min to remove cyclohexane in the solution, then cooled to below 60°C, 10 mL of a methanol solution containing 126.5 mg NaOH and 112.5 mg NH4F was dripped dropwise into the three-necked flask, and the mixture was heated to 110°C and kept warm for 50 min to remove methanol in the solution.

[0094] The vacuum was initially evacuated for 30 minutes, and the temperature was raised to 300° C. in an argon atmosphere and kept at this temperature for 90 minutes, so as to coat the surface of the second particle with a third shell layer containing NaYF4:Yb,Tm.

[0095] After the reaction is completed, turn off the heating. After the solution is cooled to room temperature, the solution in the three-necked flask is divided into centrifuge tubes, an equal volume of anhydrous ethanol is added, and high-speed centrifugation is performed to obtain a precipitate, which is then washed several times with cyclohexane and anhydrous ethanol to obtain NaErF4@NaYbF4@NaYbF4:20%Nd@NaYF4:19.5%Yb,0.5%Tm upconversion nanoparticles (C@S1@S2@S3), which are finally stored in cyclohexane.

[0096] Example 2

[0097] In order to further optimize the C@S1@S2@S3 to achieve efficient green, red and blue up-conversion luminescence performance under different light switching of 1550nm, 808nm and 980nm lasers, this embodiment experimentally determines the influence of the thickness of each specific shell layer and the concentration of rare earth dopants in the luminescent layer on the luminescence performance of C@S1@S2@S3 nanomaterials.

[0098] 1. The thickness of NaYbF4 in NaErF4@NaYbF4 particles was regulated by the input amount of rare earth ion Yb, and its green luminescence performance under 1550nm laser excitation was explored. Specifically: According to the method provided in Example 1, a batch of NaErF4 nanoparticles were synthesized, and 0.3mmol, 0.5mmol and 1mmol of Yb(CH3COO)3 were added respectively to prepare NaErF4@NaYbF4 particles. The first shell S1 with thickness d of 2.5nm, 3.9nm and 6.1nm was obtained by calculation through particle size distribution.

[0099] The NaErF4@NaYbF4 particles were dispersed in cyclohexane solution, and the solution was analyzed by fluorescence spectrum using FS5 fluorescence spectrometer. Figure 3 As shown in the figure, when the thickness of the NaYbF4 layer increases from 2.5nm to 3.9nm, the absolute luminescence intensity of the upconverted green light increases, but when the thickness of the NaYbF4 layer increases from 3.9nm to 6.1nm, the overly thick shell is not conducive to energy transfer, resulting in a decrease in absolute intensity. By normalizing the red light, it can be seen that with the increase in the thickness of the NaYbF4 layer, the degree of surface quenching decreases, which enhances the cross relaxation of Er ions, so the red light emission intensity increases, resulting in a decrease in the green-red ratio ( Figure 3 b illustration).

[0100] Based on the above analysis results, we finally selected the NaYbF4 layer (S1) with a thickness of 2.5 nm for the optimal luminescence effect.

[0101] 2. On the basis of the NaYbF4 layer, the thickness of the NaYbF4:Nd layer is changed by adjusting the amount of rare earth ions Yb and Nd, which specifically includes the following steps: on the basis of NaErF4@NaYbF4 particles, Yb source and Nd source with a total molar amount of 0.2mmol, 0.3mmol and 0.5mmol are added to synthesize C@S1@S2 nanoparticles. The thickness of NaYbF4:Nd(S2) is calculated to be 2.7nm, 4.0nm and 6.8nm respectively through particle size distribution.

[0102] The C@S1@S2 nanoparticles with the same concentration and three different thicknesses were dispersed in cyclohexane, and the solution was analyzed by fluorescence spectroscopy using an FS5 fluorescence spectrometer. The analysis results are shown in Figure 2. Figure 4 As shown in the figure, under 808nm laser excitation, when the thickness of the NaYbF4:Nd layer increases from 2.7nm to 6.8nm, the absolute luminescence intensity of the upconverted red light gradually increases. We believe that this is because as the thickness of the NaYbF4:Nd(S2) layer increases, the number of photons absorbed by Nd ions at 808nm increases, and more photons are transferred to the Er ions in NaErF4, resulting in stronger red light emission. At the same time, by normalizing the green light, as the thickness of the NaYbF4:Nd layer increases, the number of absorbed photons increases, the relative intensity of the red light increases, and the red-green ratio is enhanced ( Figure 4 b illustration).

[0103] like Figure 5 As shown in the figure, under 1550nm laser excitation, when the thickness of the NaYbF4:Nd layer increases, the absolute luminous intensity of the up-converted green light gradually decreases. We believe that this is because as the thickness of the luminescent layer NaYbF4:Nd(S2) increases, the ability of the luminescent core layer NaErF4 to absorb 1550nm laser decreases, resulting in a decrease in green light emission; at the same time, by normalizing the green light, it can be seen that as the thickness of the NaYbF4:Nd layer increases, the relative intensity of the green light decreases very little, so it has little effect on the green-red ratio ( Figure 5 b illustration).

[0104] Therefore, considering the luminescence performance of 808nm and 1550nm, NaYbF4:Nd(S2) with a thickness of about 4.0nm was finally selected to achieve the optimal luminescence effect.

[0105] 3. The raw material input amounts of rare earth ions Yb and Nd in the NaYbF4:Nd layer were regulated to achieve different Yb doping concentrations, which were 30% Yb, 50% Yb and 80% Yb, respectively. The cyclohexane solutions of C@S1@S2 nanoparticles with the same concentration and three different Yb doping concentrations were subjected to fluorescence spectral analysis using an FS5 fluorescence spectrometer.

[0106] like Figure 6As shown in the figure, under 808nm laser excitation, when the Yb doping concentration in NaYF4:x%Yb,Nd increases from 30% to 80%, the absolute luminescence intensity of the up-converted red light gradually increases. We believe that this is because as the Nd ions in the shell NaYF4:x%Yb,20%Nd(S2) absorb the energy from the 808nm laser, more Yb ions transfer energy to the innermost Er ions. Due to the high doping of Er ions, cross relaxation between Er ions occurs, thereby emitting stronger red light. At the same time, b is the normalization of the green light at 545nm. The normalized results show that as the Yb doping concentration in the S2 luminescent layer NaYF4:x%Yb,Nd increases, the relative intensity of the red light increases, thus leading to an enhancement of the red-green ratio ( Figure 6 b illustration).

[0107] like Figure 7 As shown in the figure, under 1550nm laser excitation, when the Yb doping concentration in NaYF4:x%Yb,Nd increases from 30% to 80%, the absolute luminous intensity of the up-converted green light increases. We believe that this is because as the Yb doping concentration in NaYF4:x%Yb,20%Nd increases, the luminescent core layer NaErF4 absorbs the energy of the 1550nm laser, and the Yb ions quench the energy of the red light level of the Er ions through the energy migration process, resulting in enhanced green light emission; at the same time, b is the normalization of the red light at 655nm. The normalized results show that as the Yb doping concentration in NaYF4:x%Yb,Nd increases, the relative intensity of the green light increases, and the green-red ratio increases ( Figure 7 b illustration).

[0108] Based on the above characterization results and the luminescence performance under 808nm and 1550nm excitation, the optimal luminescence effect is achieved when the Yb doping concentration in the S2 layer is 80%.

[0109] 4. Based on NaErF4@NaYbF4@NaYbF4:20%Nd particles, the effect of S3 layer thickness on blue light emission was investigated by adjusting the added amounts of Y, Yb and Tm.

[0110] The total amount of NaYF4:19.5%Yb,0.5%Tm was adjusted to 0.5mmol, 1.5mmol and 2.5mmol respectively to synthesize C@S1@S2@S3 nanoparticles. The thickness of the luminescent layer NaYF4:19.5%Yb,0.5%Tm was calculated to be 17.8nm, 25.3nm and 35.3nm respectively through particle size distribution.

[0111] The cyclohexane solutions of C@S1@S2@S3 nanoparticles with the same concentration and three different thicknesses were analyzed by fluorescence spectroscopy using an FS5 fluorescence spectrometer.

[0112] like Figure 8 As shown in the figure, under 980nm laser excitation, when the thickness of the S3 layer increases from 17.8nm to 35.3nm, the absolute luminous intensity of the upconverted blue light gradually increases. We believe that this is because as the thickness of the luminescent layer S3 increases, the energy of 980nm is absorbed in the outermost layer and will no longer be transferred to the inner shell layer, resulting in enhanced blue light emission; at the same time, b is the normalized result, and it can be seen that as the thickness of S3 increases, the relative intensity of blue light increases, thus leading to an enhancement of the blue-red ratio ( Figure 8 b illustration).

[0113] like Fig. 9 As shown in the figure, under 808nm laser excitation, when the thickness of the S3 layer increases from 17.8nm to 35.3nm, the absolute luminescence intensity of the upconverted red light gradually decreases. We believe that this is because as the thickness of the luminescent layer S3 increases, the ability of the shell NaYbF4:20%Nd(S2) to absorb 808nm laser decreases, resulting in a decrease in the red light emission; at the same time, b is the normalized result, and it can be seen that as the thickness of S3 increases, the relative intensity of the red light decreases, thus resulting in a decrease in the red-to-blue ratio ( Fig. 9 b illustration).

[0114] like Fig.10 As shown in the figure, under 1550nm laser excitation, when the thickness of the S3 layer increases from 17.8nm to 35.3nm, the absolute luminous intensity of the up-converted green light gradually weakens. We believe that this is because as the thickness of the luminescent layer S3 increases, the ability of the luminescent core layer to absorb the 1550nm laser decreases, resulting in a weakening of the green light emission; at the same time, b is the normalized result, and it can be seen that as the thickness of S3 increases, the relative intensity of the green light weakens very little, so it has little effect on the green-red ratio ( Fig.10 b illustration).

[0115] Based on the above characterization results and the luminescence performance under 980nm, 808nm and 1550nm excitation, NaYF4:19.5%Yb,0.5%Tm(S3) with a thickness of 25.3nm was selected as the optimal luminescence effect.

[0116] 5. C@S1@S2@S3 nanoparticles were synthesized by adjusting the Yb doping amount in the NaYF4:x%Yb,0.5%Tm layer to 9.5%, 19.5% and 49.5% respectively. The cyclohexane solutions of C@S1@S2@S3 nanoparticles with three different Yb doping concentrations were subjected to fluorescence spectral analysis using an FS5 fluorescence spectrometer.

[0117] like Fig.11 As shown in the figure, under 980nm laser excitation, when the Yb doping concentration in the NaYF4:Yb,Tm layer increases from 9.5% to 49.5%, the absolute luminous intensity of the up-converted blue light gradually increases. We believe that this is because as the Yb doping concentration in the luminescent layer NaYF4:Yb,Tm (S3) increases, it is more conducive to the wavelength of blue light to move to a shorter wavelength. Therefore, the absolute intensity around 450nm is mainly observed. It can be seen that with the increase of Yb concentration, the blue light increases; at the same time, b is the normalized result. It can be seen that with the increase of Yb doping concentration in the S3 layer, the relative intensity of blue light increases, thus leading to an enhancement of the blue-red ratio ( Fig.11 b illustration).

[0118] like Fig.12 As shown in the figure, under 808nm laser excitation, when the Yb doping concentration in the NaYF4:Yb,Tm layer increases from 9.5% to 49.5%, the absolute luminous intensity of the up-converted red light gradually decreases. We believe that this is because as the Yb doping amount in the luminescent layer NaYF4:Yb,Tm (S3) increases, the ability of the S2 layer to absorb 808nm laser decreases, resulting in a decrease in the red light emission; at the same time, b is the normalized result, and it can be seen that as the Yb ion concentration in the S3 layer increases, the relative intensity of the red light decreases, thus resulting in a decrease in the red-to-blue ratio ( Fig.12 b illustration). This is because as the concentration of Yb ions in the S3 layer increases, the S2 layer absorbs the 808nm laser and is then 3+ -Yb 3+ The possibility of energy transfer to the S3 layer and exciting Tm ions is enhanced, resulting in enhanced blue light emission.

[0119] like Fig.13 As shown in the figure, under 1550nm laser excitation, when the Yb doping amount in the NaYF4:Yb,Tm layer increases from 9.5% to 49.5%, the absolute luminescence intensity of the up-converted green light gradually increases. We believe that this is because as the Yb ion concentration in the S3 layer increases, the luminescent core layer NaErF4 absorbs the energy of the 1550nm laser, and the energy of the red light level of the Er ions quenched by the Yb ions increases, resulting in enhanced green light emission; at the same time, b is the normalized result, and it can be seen that as the Yb doping concentration in the S3 layer increases, the relative intensity of the green light increases very little, so it has little effect on the green-red ratio ( Fig.13 b illustration).

[0120] Based on the above characterization results and the luminescence performance under 980nm, 808nm and 1550nm excitation, the Yb doping concentration of NaYF4:x%Yb,0.5%Tm(S3) layer is 19.5% for the optimal luminescence effect.

[0121] In summary, by regulating the luminescent shell and Yb doping concentration, three types of C@S1@S2@S3 UCNPs with optimal luminescence performance were successfully synthesized, among which the thickness of the NaYbF4 (S1) layer was determined to be 2.5nm, the thickness of NaYbF4:20%Nd (S2) was 4.0nm, and the thickness of the NaYF4:19.5%Yb,0.5%Tm (S3) layer was 25.3nm.

[0122] The present invention further studies that under the laser irradiation of three lasers (1550, 808, 980 nm), as the laser power density continues to increase, the luminescence intensity of the UCNPs cyclohexane solution in the cuvette continues to increase, and the luminescence color does not change at all, such as Fig.14 shown.

[0123] The particle material of the rare earth doped light switchable upconversion nanocomposite UCNPs preparation process provided in Example 1 was observed by transmission electron microscopy (TEM). The observation results are as follows: Fig.15 As shown, it can be seen that the NaErF4(C) core is a spherical nanoparticle and is uniformly dispersed, with a particle size of about 16 nm ( Fig.15 After the first shell layer is coated, the particles are still spherical and uniformly dispersed, with a particle size of about 21 nm ( Fig.15 b); After coating the second shell, the particle size grows to 29 nm ( Fig.15 c); after coating the third shell layer, upconversion nanoparticles with uniform size are obtained, with a particle size of about 86nm ( Fig.15 d); the inset of d is an image measured under a high-magnification electron microscope. The measurement showed that the lattice spacing of the UCNPs is 0.53nm, corresponding to the (100) crystal plane of the crystal.

[0124] The nanoparticles UCNPs prepared in step 4 were tested in HAADF-STEM. The test results are as follows: Fig.16 As shown, Er 3+ The element distribution is mainly concentrated in the core part, while Y 3+ , Yb 3+ 、Nd 3+ The element signals are almost scattered in every layer of the particles. 3+ The distribution of elements is less, indicating the formation of a core-shell multilayer structure.

[0125] Example 2

[0126] This embodiment provides the application of the above rare earth doped light switchable upconversion nanocomposite particles in tumor cell imaging and treatment. A composite material adsorbed with a photosensitizer is prepared according to the following preparation method:

[0127] Step 1: Synthesis of mesoporous silica modified upconversion nanoparticles (UCNPs@mSiO2):

[0128] Weigh 200 mg of hexadecyltrimethylammonium bromide CTAB solid powder into a 100 mL beaker, then add 20 mL of ultrapure water and stir at 70 ° C for 20 min to completely dissolve it into a colorless and transparent solution. Then add 2 mL (about 50 mg) of the synthesized UCNPs cyclohexane solution dropwise into the beaker, stir vigorously overnight at room temperature to remove the cyclohexane in the solution to form a UCNPs-CTAB micelle solution, and the final solution after overnight is a clear solution.

[0129] Then transfer it to a 250mL three-necked flask, add 40mL ultrapure water, 6mL anhydrous ethanol, 300μL NaOH (2mol / L) aqueous solution, stir for 30min in a 70℃ oil bath and reflux. Then add 400μL of ethyl silicate TEOS dropwise and react for 1.5h. After the reaction is completed, pour the solution into a centrifuge tube, centrifuge at high speed to obtain a white precipitate, and then wash it several times with anhydrous ethanol solution to remove free silica and CTAB template (highly toxic to cells).

[0130] In order to remove the CTAB in the mesoporous channels, the solid product was placed in 40 mL of acidic ethanol solution (pH = 1.4-1.5), ultrasonically dissolved, and then refluxed for 3 hours in a 60 ° C oil bath. After the reflux, the precipitate was taken by high-speed centrifugation and then washed three times with anhydrous ethanol. The whole process needs to be repeated about three times in order to fully remove the CTAB template and reduce its cytotoxicity. Finally, the white precipitate was stored in 10 mL of ethanol or water to obtain mesoporous silica-modified UCNPs.

[0131] Step 2: Synthesis of UCNPs@mSiO2-MC540-FePc nanosystem:

[0132] First, take an ethanol solution containing 5 mg of UCNPs@mSiO2 and centrifuge at high speed to retain the precipitate. Then, weigh 0.6 mg of iron phthalocyanine FePc and 0.6 mg of merocyanine MC540 solid powder and dissolve them in 2 mL of dimethyl sulfoxide (DMSO) solution under light-proof conditions, and ultrasonically disperse them for 20 minutes. Finally, transfer the ultrasonic solution to the precipitate of UCNPs@mSiO2 and ultrasonically disperse them for another 10 minutes.

[0133] The mixed solution was transferred to a 5 mL single-mouth round-bottom flask and stirred rapidly for 12 h at room temperature (25 ° C) in the dark. After the adsorption, the precipitate was centrifuged at high speed, dissolved and dispersed with ultrapure water by ultrasonic, and then centrifuged at high speed to precipitate. This process needs to be performed at least three times to remove free MC540, FePc and DMSO solvent, and finally dissolved in 1 mL of ultrapure water to obtain UCNPs@mSiO2-MC540-FePc nanosystem.

[0134] Fig.17 TEM characterization results of UCNPs@mSiO2, such as Fig.17 As shown, the UCNPs@mSiO2 nanoparticles are single and uniformly dispersed, and the thickness of the silicon layer is about 15nm.

[0135] Fig.18 is the N2 adsorption / desorption isotherm of UCNPs@mSiO2, such as Fig.18 As shown in the figure, according to the IUPAC classification of physical adsorption isotherms for porous materials, UCNPs@mSiO2 mesoporous materials belong to the typical IV type adsorption isotherm, indicating that the synthesized silica is a mesoporous structure. Then, according to the BET method, the specific surface area of ​​the nanoparticles is calculated to be 690.36 m 2 / g, and the average pore size is about 3.414nm.

[0136] Fig.19 The infrared thermal images of UCNPs@mSiO2-MC540-FePc solutions with different concentrations changing with time under 808nm laser irradiation are shown in Figure 2. Fig.19 As shown, at different concentrations, as the experimental time increases, the temperature of the system continues to rise. When the concentration is as high as 300 μg / mL, the maximum temperature can reach nearly 50°C.

[0137] The 1,3-diphenylisobenzofuran (DPBF) probe was used to detect the release ability of singlet oxygen from UCNPs@mSiO2-MC540-FePc. The DPBF probe has a strong absorption at 417 nm, and the singlet oxygen ( 1 O2) will react with the probe to reduce the absorption intensity at 417nm, which can be used to infer the absorption of nanomaterials in solution. 1 The release of O2. Fig. 20 As shown in the figure, after irradiation of UCNPs@mSiO2-MC540-FePc nanomaterials at 1550nm for 30min, it can be clearly seen from the spectrum that the absorption around 417nm has decreased significantly, indicating that UCNPs@mSiO2-MC540-FePc can produce singlet oxygen by emission and reabsorption under 1550nm excitation.

[0138] like Fig.21 As shown, under different experimental conditions, the ability to produce singlet oxygen is also different, and the ability to produce singlet oxygen under 1550nm excitation is the best. In the pure DPBF solution, no matter what the excitation situation is, the absorption around 417nm has almost no decrease, that is to say, the amount of probe is almost not consumed. The control group shows that DPBF has no effect on the production of singlet oxygen. In the case of successful adsorption of dual photosensitizers (MC540, FePc), it can be clearly observed that under 1550nm excitation, with the increase of time, the release amount of DPBF can reach about 70% at the fastest 30min, while the release amount in the three cases of no light, 980nm, and 808nm irradiation is less than 20%. According to the above mechanism and experimental results, 1550nm irradiation plays an important role in the production of singlet oxygen. Under 1550nm excitation, the light emission generated by UCNPs can be effectively absorbed by the photosensitizer MC540, thereby producing singlet oxygen ( 1 O2), providing a theoretical basis for subsequent cell experiments.

[0139] Nanomaterials need to be used in subsequent biological applications, so the nanoparticles need to be harmless to the cells used in the application. HeLa cells were incubated with different concentrations of UCNPs@mSiO2-MC540-FePc nanoparticles (0, 50, 100, 200, 300 μg / mL) for 24 hours, and then the CCK-8 cytotoxicity assay was used to detect the survival rate of HeLa cells. The test results are as follows: Fig. 22 As shown, even when the nanoparticle concentration is as high as 300 μg / mL, it will hardly affect the activity of HeLa cells, and the cell survival rate will not be less than 95%, indicating that the composite material UCNPs@mSiO2-MC540-FePc is almost non-toxic and has good biocompatibility.

[0140] In vitro programmable photodynamic-photothermal therapy of UCNPs@mSiO2-MC540-FePc nanoparticles was studied. Six groups of experimental conditions were designed. UCNPs@mSiO2-MC540-FePc was prepared into a solution with a concentration of 200 μg / mL and mixed with HeLa cells. The viability of HeLa cells was tested under six different experimental conditions (no laser means no illumination, 980nm means 980nm irradiation, PTT means 1550nm irradiation, PDT means 808nm irradiation, PDT+PTT means simultaneous 1550nm and 808nm irradiation, PDT→PTT means 1550nm irradiation and then 808nm irradiation).

[0141] according to Fig.23It can be seen that under these six experimental conditions, photothermal therapy under 808nm irradiation and photodynamic therapy under 1550nm irradiation have certain killing effects on tumor cells, and the photodynamic therapy effect is better than the photothermal therapy effect. For the programmable tumor therapy corresponding to the light-switching material we designed, PDT→PTT (first 1550nm irradiation, then 808nm irradiation), such a therapeutic effect is better than the simultaneous two treatments, that is, PDT+PTT (1550nm and 808nm simultaneous irradiation). This is because after the first photodynamic therapy (PDT), the lysosomes are ruptured. At this time, more particles are avoided from being digested and degraded by cells. After photothermal therapy (PTT), there will be better therapeutic effects. These experimental results show that UCNPs@mSiO2-MC540-FePc has a therapeutic effect on HeLa cells. The therapeutic effect of using PDT→PTT is better than the other five treatment methods, proving that programmable therapy has good feasibility and better therapeutic effects.

[0142] The results show that the above-mentioned triple-excitation-triple-emission upconversion nanomaterials regulated by lanthanide activators based on energy migration pathways have obvious synergistic therapeutic effects, no obvious toxicity, and have good anti-tumor cell therapeutic effects.

[0143] The method provided by the present invention is simple, fast, highly safe, and the prepared nanoparticles are of high purity. The entire synthesis process is fast and simple, and no special reaction equipment is required. From the perspective of industrial production, the time of the synthesis process can be greatly shortened, the entire production process is simple, and the cost performance of the product is improved. At the same time, nitrogen is introduced as a protective gas during the synthesis to avoid the generation of other impurities. The generated nanocrystal particles are pure and have multiple uses, and can significantly improve the diagnosis and treatment effect, and realize the diagnosis and treatment of tumor cells.

[0144] Comparative Example 1

[0145] Synthesis of NaErF4: Yb (20%), Nd (20%), Tm (0.5%):

[0146] All elements of Er(CH3COO)3, Tm(CH3COO)3, Nd(CH3COO)3, and Yb(CH3COO)3 were added together, and the upconversion fluorescence emission spectra of NaErF4:Yb(20%), Nd(20%), and Tm(0.5%) nanoparticles were measured under excitation of 808nm, 980nm, and 1550nm lasers.

[0147] Depend on Fig.24 It can be observed that no red light is generated under 808nm excitation; Fig.26 It can be observed that no green light is generated under 1550nm excitation.

[0148] Comparative Example 2

[0149] Synthesis of NaErF4@NaYbF4:Nd@NaYbF4@NaYF4:19.5%Yb,0.5%Tm

[0150] The first and second shells of the designed and synthesized NaErF4@NaYbF4@NaYbF4:Nd@NaYF4:Yb,Tm(C@S1@S2@S3) nanomaterials were swapped to synthesize NaErF4@NaYbF4:Nd@NaYbF4@NaYF4:19.5%Yb,0.5%Tm nanomaterials.

[0151] The upconversion fluorescence emission spectra of C@S2@S1@S3 nanoparticles were measured under 808nm, 980nm, and 1550nm laser excitation. Fig. 27 It can be observed that no red light is generated under 808nm excitation; Fig.29 It can be observed that no green light is generated under 1550nm excitation.

[0152] In summary, the light-switchable up-conversion nanocomposite particles provided by the present invention have a core-shell structure, wherein the core is NaErF4 nanoparticles, and the surface of the core is sequentially coated with three shell layers, and each shell layer contains different rare earth elements. Through the design of different rare earth doping elements, the light-switchable up-conversion nanocomposite particles provided by the present invention independently emit red light, blue light and green light under the excitation of three near-infrared light sources (808nm, 980nm and 1550nm), realizing a unique three-excitation-three-emission luminescence characteristic, and the emission color is independent of the power density of the laser.

[0153] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A rare earth doped light switchable upconversion nanocomposite particle, characterized in that: The composite particle has NaErF4 nanoparticles as the core, and the outer surface of the core is sequentially coated with a first shell layer, a second shell layer and a third shell layer; The first shell is NaYbF4; The second shell is NaYbF4:Nd; The third shell is NaYF4:Yb,Tm.

2. The rare earth doped light switchable upconversion nanocomposite particles according to claim 1, characterized in that: The thickness of the first shell is 2.5-6.1 nm; The thickness of the second shell is 2.7-6.8 nm; The thickness of the third shell layer is 17.8-35.3 nm.

3. The rare earth doped light switchable upconversion nanocomposite particles according to claim 1, characterized in that: In the second shell layer, the molar ratio of Yb to Nd is 8:

2.

4. The rare earth doped light switchable upconversion nanocomposite particles according to claim 1, characterized in that: In the third shell layer, the molar ratio of Y, Yb and Tm is 80:19.5:0.

5.

5. A method for preparing rare earth doped light-switchable upconversion nanocomposite particles according to any one of claims 1 to 4, characterized in that: The steps include: Step 1, mixing an Er source, an inorganic fluoride and a sodium source and reacting them to prepare NaErF4 nanoparticles; Step 2, dispersing NaErF4 nanoparticles in a solvent, adding a Yb source, an inorganic fluoride and a sodium source, so that the surface of the NaErF4 nanoparticles is coated with a first shell layer containing NaYbF4, to obtain first particles; Step 3, dispersing the first particles in a solvent, adding a Yb source, a Nd source, an inorganic fluoride and a sodium source, so that the surface of the first particles is coated with a second shell layer containing NaYbF4:Nd, to obtain second particles; Step 4: dispersing the second particles in a solvent, adding a Y source, a Yb source, a Tm source, an inorganic fluoride and a sodium source, so that the surface of the second particles is coated with a third shell layer containing NaYF4:Yb, Tm, and obtaining the rare earth doped upconversion nanocomposite material.

6. The preparation method according to claim 5, characterized in that: In step 2, the molar ratio of the NaErF4 nanoparticles to the Yb source is 0.1:(0.3-1).

7. The preparation method according to claim 5, characterized in that: In step 3, the molar ratio of the first particles to the Yb source is 0.05:(0.16-0.4), and the molar ratio of the first particles to the Nd source is 0.05:(0.04-0.1).

8. The preparation method according to claim 5, characterized in that: In step 4, the molar ratio of the second particles to the Y source is 0.03:(0.4-2), the molar ratio of the second particles to the Yb source is 0.03:(0.05-0.5), and the molar ratio of the second particles to the Tm source is 0.03:(0.002-0.02).

9. Use of the rare earth doped light-switchable upconversion nanocomposite particles according to any one of claims 1 to 4 in the preparation of products for tumor cell imaging and treatment.

10. The use according to claim 9, characterized in that: The rare earth doped light switchable up-conversion nanocomposite particles have mesoporous channels on their surfaces, and one or more of photosensitizers, anti-tumor drugs and radiotherapy sensitizers are adsorbed in the mesoporous channels.

Citation Information

Patent Citations

  • Excited light regulated red-green emitting rare earth up-conversion nanoparticle and preparation method thereof

    CN107739603A

  • Multi-color tunable upconversion nanophosphor

    US20230037132A1